Costly Control: An Examination of the Trade-off Between Control Investments and Residual Risk in Interfirm Transactions - Anderson, Shannon W.; Dekker, Henri C.; Van den Abbeele, Alexandra (Management Science, 2017)
Transaction cost economics predicts that investments in management control will enable risky interfirm transactions. Risk is rarely eliminated, because firms trade off costs of management control and expected costs of control loss (together, the “cost of control”). The resultant solution typically comprises a mix of control investments with residual performance and residual relational risks. Transaction cost economics also predicts that the control-residual risk trade-off will vary with the cost of control. We use survey data on 287 risky information technology transactions to test whether the control-residual risk trade-off varies predictably with two partnership-specific factors that proxy for variation in the cost of control: prior ties between exchange partners and the criticality of strategic resources to the transaction. The results support the hypotheses, providing novel evidence on trade-offs that managers make when investing in management controls while also prudently accepting some risks. This paper was accepted by Mary Barth, accounting.